CITRAAN DALAM KUMPULAN SAJAK ORGASMAYA KARYA HASAN ASPAHANI - Yeni Maulina (Madah: Jurnal Bahasa dan Sastra, 2016)
Imagery is an important element in a poem. An idea that is originally abstract can be conceived and expressed through imagery. Imagery is generated through expression of words so that readers can easily imagine it. This study aims to determine types of imagery contained in the Orgasmaya anthology of Hasan Aspahani’s work. The method used in this research is the descriptive qualitative method. The research findings reveal that of the 74 poems that were analyzed, there are 74 data fragments of the poems containing imagery. There are 11 fragments of the poems containing visual imagery, 22 fragments containingauditory imagery, 4 fragments containing olfactory imagery, 5 fragments containing feeling imagery, 7 fragments containing palpation imagery, and 25 fragments containing motion imagery. Based on the analysis of imagery on the Orgasmaya poem anthology of Hasan Aspahani’s work, the most appeared imagery in the poems is motion imagery. It is due to the fact that the poets are able to visualize motions to readers which described through the proper choices of diction to see the beauty and natural phenomena, daily life, and social conflict as the building of imagery in his poems.